2020
DOI: 10.1177/2309499020906745
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic procedures could delay the need for a subsequent knee arthroplasty in older patients with end-stage osteoarthritis

Abstract: Background/objective: Arthroscopic surgery in knee osteoarthritis is controversial with many studies refuting its efficacy in recent literature. This study aims to evaluate the mean duration to knee arthroplasty, and the effect of microfracture on the need for subsequent knee arthroplasty in patients above the age of 55 undergoing arthroscopic procedures for osteoarthritis. Methods: One hundred and nine consecutive patients with diagnosed osteoarthritis who underwent arthroscopic surgery performed from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Lateral wedge insoles have been found to reduce MME and could also supplement a conservative treatment of knee OA, as they could potentially delay the degenerative process [ 50 ]. However, arthroscopic debridement and osteotomies around the knee are also being employed in some instances in moderate knee OA before a TKR is required [ 51 , 52 ]. Wang et al [ 53 ], in a retrospective review of 131 patients who had undergone arthroscopic surgery for knee OA and were followed up for 4 years, found that in regard to pain relief, arthroscopic surgery was also beneficial in patients with major MME (> 3 mm).…”
Section: Knee Pathologies and Mementioning
confidence: 99%
“…Lateral wedge insoles have been found to reduce MME and could also supplement a conservative treatment of knee OA, as they could potentially delay the degenerative process [ 50 ]. However, arthroscopic debridement and osteotomies around the knee are also being employed in some instances in moderate knee OA before a TKR is required [ 51 , 52 ]. Wang et al [ 53 ], in a retrospective review of 131 patients who had undergone arthroscopic surgery for knee OA and were followed up for 4 years, found that in regard to pain relief, arthroscopic surgery was also beneficial in patients with major MME (> 3 mm).…”
Section: Knee Pathologies and Mementioning
confidence: 99%
“…[7][8][9][10] Case series suggest arthroscopic surgery can delay more invasive operations for OA of the knee, such as TKA or osteotomy (limb realignment), and this message is repeated in peer-reviewed journal articles and patient information materials. [17][18][19][20][21][22] Conversely, data from longitudinal cohort studies suggest arthroscopic surgery among patients with or at risk of developing OA of the knee may increase the incidence of TKA when compared with similar patients who did not receive arthroscopic surgery. 23,24 Clinical practice guidelines for OA do not address this discrepancy.…”
Section: Introductionmentioning
confidence: 99%